Endocardial pacing compared to epicardial left ventricle pacing and right ventricle pacing: a single center long term experience in a pediatric population. (14th October 2021) - Gatti, P; Eliasson, H; Gadler, F
Abstract: Introduction: Complete atrioventricular block (CAVB), either congenital or post heart surgery, are the main indications for cardiac pacing in the pediatric population. Epicardial pacing is preferred in small infants or for specific cardiac anomalies and some studies highlight a superior contraction pattern when pacing epicardially from the left ventricular apex region [1–3]. Endocardial pacing is more frequently used in children with a weight >20 kg and is less invasive [4]. Paced QRS duration seems to be independently associated with ventricular dysfunction irrespective of location or age at device implantation [5]. Purpose: Describe the echocardiographic and electrocardiographic changes after switch from epicardial to transvenous pacing in a pediatric population with CAVB. Methods: Children (0–18 years), who underwent a switch from left- (LV) or right ventricle (RV) epicardial pacing to transvenous pacing at our center, were retrospectively studied. Clinical, ECG- and echocardiographic parameters before and after the switch of the PM-system were collected as well as the most recent FU data. Left ventricular end-diastolic diameter (LVDD) and fractional shortening (FS) values were transformed to a body surface-related and age-related z-score (z), respectively. Results: Fifteen patients with CAVB who received an epicardial pacemaker (60% congenital, 40% post-cardiac surgery) were converted to a transvenous system at our center (2005–2021). The median age at the switch was 6.8 (2–13) years with a median weight of 21 (9–62) kg. The epicardial lead location was more frequently the RV wall (60%) than the LV wall (40%). The RV outflow tract and interventricular septum were the most common locations (73%) for the endocardial leads. The mean QRS duration during epicardial stimulation was 150 (IQR 26) ms vs. a median QRS duration with the transvenous system of 136 (IQR 19) ms and a median delta QRS duration of 13ms. A detailed comparison between RV and LV epicardial pacing are reported in Figure 1. Children with post-surgical AV block had a broader median QRS duration, both with epicardial and endocardial stimulation. Before the switch, there was only one abnormal observation of FS less than −2 z with normal LVDD. At the last available follow-up (mean time 7 years), all the children had normal LVDD and only one had FS less than −2 z. Conclusions: Our report of pediatric patients after switch from epi to endo pacing, shows good results in terms of QRS duration with no significant echocardiographic or clinical evidence of deterioration of the cardiac function. Due to the small sample size the results could serve as a hypothesis generator, but larger prospective studies are needed to evaluate the electrocardiographic and echocardiographic impact of transvenous - compared to epicardial pacing. Funding Acknowledgement: Type of funding sources: None.